2022
DOI: 10.2196/35628
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Effects of the Use of a Step Count–Specific Smartphone App on Physical Activity and Weight Loss: Randomized Controlled Clinical Trial

Abstract: Background Some studies on weight loss promotion using smartphone apps have shown a weight loss effect but not an increase in physical activity. However, the long-term effects of smartphone apps on weight loss and increasing physical activity have not been rigorously examined to date. Objective The aim of this study was to assess whether the use of a smartphone app will increase physical activity and reduce body weight. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In 2023, 6.92 billion people worldwide own a smartphone, representing 86.29% of the global population ( 17 ). Fitness apps have gained popularity among smartphone users, with some proving highly effective for increasing physical fitness ( 18 ) and physical activity levels ( 19 ). While some apps are designed for the general population and may present challenges for those with health conditions, there are also apps that are specifically helpful for managing certain conditions like T1DM.…”
Section: Introductionmentioning
confidence: 99%
“…In 2023, 6.92 billion people worldwide own a smartphone, representing 86.29% of the global population ( 17 ). Fitness apps have gained popularity among smartphone users, with some proving highly effective for increasing physical fitness ( 18 ) and physical activity levels ( 19 ). While some apps are designed for the general population and may present challenges for those with health conditions, there are also apps that are specifically helpful for managing certain conditions like T1DM.…”
Section: Introductionmentioning
confidence: 99%
“…In the era of rapid information technology advancement, numerous high-level hospitals have leveraged mobile health platforms to offer post-discharge patients health consultations, information recording, online guidance, and various remote preventative, therapeutic, and rehabilitative health services [ 8 , 10 , 11 ]. The widespread adoption of these online services as supplementary medical resources has significantly benefited patients, partly fulfilling their health needs.…”
Section: Introductionmentioning
confidence: 99%
“…With at least 2.8 million people dying each year as a result of being overweight or obese [ 1 ], fitness apps are becoming increasingly important to encourage regular physical exercise [ 2 ] and monitor physiotherapy [ 3 ]. One study found that the use of smartphone fitness apps was associated with both increases in physical activity and significant reductions in body weight and body mass index [ 4 ]. Many outdoor cardio activities can be tracked with relative ease using a device with an embedded global navigation satellite system (GNSS) receiver [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%